2011
DOI: 10.1200/jco.2011.29.15_suppl.e19611
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and insulin resistance in pediatric acute lymphoblastic leukemia worsens during maintenance therapy.

Abstract: Background-Pediatric acute lymphoblastic leukemia (ALL) survivors are at increased risk for the metabolic syndrome (MS). To establish the trajectory of development during active treatment, we followed patients longitudinally over the first year of maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Until now, most studies investigating body composition had been conducted in ALL and lymphoma survivors and have shown a wide variation of obesity, even up to about 50%. The authors observed higher fat mass and lower lean mass in these patients after treatment completion compared with healthy subjects . Determining body composition and its association with circulating adipokines could be of clinical importance.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Until now, most studies investigating body composition had been conducted in ALL and lymphoma survivors and have shown a wide variation of obesity, even up to about 50%. The authors observed higher fat mass and lower lean mass in these patients after treatment completion compared with healthy subjects . Determining body composition and its association with circulating adipokines could be of clinical importance.…”
Section: Discussionmentioning
confidence: 89%
“…However, the literature data on the relations between body composition parameters and serum levels of adipokines in childhood cancer survivors are still scare and the results are ambiguous. Generally, authors reported an increase in leptin (positively correlated with BMI z‐score) and a decrease in adiponectin (inversely correlated with BMI z‐score) levels in patients with acute lymphoblastic leukemia after therapy completion . They suggested that corticosteroid therapy, as well as cranial irradiation used in patients with ALL causes anthropometric and metabolic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Author found that in these patients over the first year of ALL maintenance therapy demonstrated that components of the metabolic syndrome significantly worsen over time. Preventive interventions limiting increases in BMI and insulin resistance during maintenance therapy should be targeted during this time period to avoid long-term morbidity associated with the metabolic syndrome in long-term survivors [15]. Al-Tawil MM et al described the studies associating chronic hepatitis C virus (HCV) infection with lipid profile and hepatic steatosis in leukemia or lymphoma cured children.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 A group of American investigators has shown that preventive therapeutic interventions limiting the increase in BMI and insulin resistance may be particularly important during maintenance therapy. 50 These therapeutic interventions will however require more expensive prospective studies for accurate evaluation.…”
Section: Number Of Cases (%) 95% CImentioning
confidence: 99%